Revealing Intrinsic Functionalization, Structure, and Photo-Thermal Oxidation in Hexagonal Antimonene - Alcaraz, Marta; Fickert, Michael; Dolle, Christian; Changarath, Mahesh Eledath; Sánchez-Royo, Juan F.; Eggeler, Yolita M.; Abellán, Gonzalo (Small, 2024)
Antimonene is one of the more exciting members of the post-graphene family with promising applications in optoelectronics, energy storage and conversion, catalysis, sensing or biomedicine. Efforts have been focused on developing a large-scale production route, and indeed, through a colloidal approach, high-quality few-layers antimonene (FLA) hexagons have been recently obtained. However, their oxidation behavior remains unexplored, as well as their interface, inner structure, and photothermal properties. Herein, it is revealed that the hexagons have an intrinsic surface functionalization with alkyl thiols that protects the core of the hexagonal flake against oxidation, and displayed inner defects related to the crystal formation during synthesis, as confirmed by cross-sectional scanning transmission electron microscopy energy dispersive X-ray spectroscopy (STEM-EDX) and temperature-dependent X-ray photoelectron spectroscopy (XPS) and selected area electron diffraction (SAED) analysis. A comprehensive study of temperature and laser power-dependent Raman spectroscopy on varying FLA hexagon thicknesses is carried out. Thinner flakes (<20 nm) exhibited a blueshift and intensity decrease, contrasting with thicker ones resembling typical exfoliated flakes with a redshift. This work addresses a literature gap, providing insights into hexagonal FLA structure and characterization, and highlighting the influence of surface functional groups on oxidation behavior. Additionally, it emphasizes the potential of antimonene hexagons as building blocks for 2D heterostructures, including combinations with antimonene oxides and other 2D materials.
CRIS-Team Scopus Importer:2024-10-25
Keywords: 2D Pnictogens; antimonene; functionalization; oxidation; photo-thermal properties